The Effect Of Selection, Training, And Job Placement On Employee Performance At PT Wijaya Karya Beton Pasuruan - Syafrie Samsudin; Fauzan Almanshur (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the effect of selection, training, and job placement on employee performance at PT Wijaya Karya Beton Pasuruan. The background of this study is based on the company's performance fluctuations, which are reflected in the instability of business income, production realization, and company efficiency over the past five years. These conditions indicate problems in human resource management, particularly in relation to the selection, training, and job placement processes, which have not been optimal. This study uses a quantitative approach with explanatory research, involving the entire population of 80 permanent employees using saturated sampling techniques. Data collection was conducted through questionnaires and analyzed using IBM SPSS. The analysis techniques included validity, reliability, normality, linearity, multicollinearity, heteroscedasticity, multiple linear regression, t-test, F-test, and coefficient of determination tests. The results of the study show that: selection has a positive and significant effect on employee performance; training has a positive effect and is the most dominant variable in improving performance; job placement has a positive and significant effect on performance; and simultaneously, selection, training, and job placement have a significant effect on employee performance.